Nisekoi : False love. Vol. 21, To Mari - Komi, Naoshi, 1986- (Shonen Jump manga., 2017)
"Marika is ill but comes to school on Valentine's Day just to bring Raku a gift of chocolate! Once again, she presses him to respond to her feelings... But when her health reaches its limit, she is forced to return to her family's home in Kyushu. Unwilling to accept the loss of their friend, Raku and the gang take action!"--